Optics in Mexico - Jaroszewicz, Zbigniew; Tepichín-Rodriguez, Eduardo; Ojeda-Castaneda, Jorge (Photonics Letters of Poland, 2015)
This editorial contains the overview of the contents of the current issue of Photonics Letters of Poland devoted to optics in Mexico.